Mitochondrial proteomics of nasopharyngeal carcinoma metastasis - Liu Jianping; Zhan Xianquan; Li Maoyu; Li Guoqing; Zhang Pengfei; Xiao Zhefeng; Shao Meiying; Peng Fang; Hu Rong; Chen Zhuchu (BMC Medical Genomics, 2012)
Abstract Background Mitochondrial proteomic alterations of nasopharyngeal carcinoma metastasis remain unknown. Our purpose is to screen mitochondrial proteins for the elucidation of the molecular mechanisms of nasopharyngeal carcinoma metastasis and the discovery of metastasis-related biomarkers. Methods Mitochondria were isolated from nasopharyngeal carcinoma metastatic (5-8F) and nonmetastatic (6-10B) cell lines, respectively. After characterization of isolated mitochondria, mitochondrial differentially expressed proteins (DEPs) were quantified by two-dimensional difference in-gel electrophoresis (2D-DIGE), and identified by peptide mass fingerprint (PMF) and tandem mass spectrometry (MS/MS). A functional enrichment analysis and a protein-protein interaction sub-network analysis for DEPs were carried out with bioinformatics. Furthermore, siRNAs transient transfections were used to suppress expressions of some up-regulated DEPs in metastatic cells (5-8F), followed by Transwell Migration assay. Results Sixteen mitochondrial DEPs including PRDX3 and SOD2 were identified. Those 5-8F cells with suppression of PRDX3 showed an increased mobility potential. The functional enrichment analyses of DEPs discovered five significant biological processes including cellular response to reactive oxygen species, hydrogen peroxide metabolic process, regulation of mitochondrial membrane potential, cell redox homeostasis and oxidation reduction, and five significant molecular functions including oxidoreductase activity, caspase inhibitor activity, peroxiredoxin activity, porin activity and antioxidant activity. A protein-protein interaction sub-network of DEPs was generated with literature data. Ten mitochondrial DEPs including PRDX3, PRDX6, SOD2, ECH1, SERPINB5, COX5A, PDIA5, EIF5A, IDH3B, and PSMC4 were rationalized in the tumor-stroma co-evolution model that mitochondrial oxidative stress directly contributes to tumor metastasis. Conclusions Sixteen mitochondrial DEPs were identified with mass spectrometry and ten of them were rationalized in the tumor-stroma co-evolution model. Those 5-8F cells with suppression of PRDX3 showed an increased mobility potential. These data suggest that those mitochondrial DEPs are potential biomarkers for NPC metastasis, and their dysregulation would play important roles in mitochondria oxidative stress-mediated NPC metastatic process.